A method for preparing modified hydroxyapatite whiskers for improving bone conduction osteogenesis activity

CN122998462APending Publication Date: 2026-10-30KUNMING UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611186460.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提供一种提升骨传导成骨活性的改性羟基磷灰石晶须制备方法,以解决现有骨修复材料力学性能差、降解与成骨再生速率不匹配、干细胞诱导分化能力不足的技术问题

Benefits of technology

1、本发明制备的锶离子Sr2+掺杂羟基磷灰石晶须,在保证羟基磷灰石晶须不变且截面是六方结构的情况下,使其晶体结构稳定、强度和韧性得以提升,满足皮质骨力学性能实际要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122998462A_ABST
    Figure CN122998462A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of modified hydroxyapatite whiskers with improved bone conduction osteogenesis activity, and belongs to the technical field of medical biomaterials. The method comprises the following steps: dissolving acetamide in ultrapure water to prepare an acetamide solution; weighing calcium salt, metal strontium salt and a phosphoric acid source according to a set molar ratio, and sequentially dissolving the calcium salt, the metal strontium salt and the phosphoric acid source in the acetamide solution, stirring and uniformly dispersing to obtain a uniformly mixed precursor solution; adding acid liquor to the obtained precursor solution to adjust the pH value to be acidic, so as to obtain an acidified precursor solution; performing a hydrothermal synthesis reaction on the obtained acidified precursor solution, collecting precipitates after the reaction, and performing aging, washing, suction filtration and drying to obtain modified hydroxyapatite whisker composite materials with improved bone conduction osteogenesis activity. The process flow of the application is simple, the product performance is excellent and stable, and the hydroxyapatite whiskers modified by the strontium salt can significantly improve the differentiation ability of rat mesenchymal stem cells, and can be used in the field of bone repair and osteogenesis materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical biomaterials technology, specifically to a method for preparing modified hydroxyapatite whiskers that enhance osteogenic activity through bone conduction. Background Technology

[0002] Traditional treatments for bone defects include autologous bone grafting, allogeneic bone grafting, and xenogeneic bone grafting; however, all three methods have limitations. While autologous bone grafting possesses natural biocompatibility, it suffers from significant individual trauma and high costs. Allogeneic bone grafting typically involves extraction from cadavers, resulting in a shortage of donors and a higher risk of immunogenicity. Xenogeneic bone, generally derived from non-human bone tissue, carries risks of viral infection and sterilization. Currently, synthetic bone is attracting considerable attention due to its advantages in eliminating viral transmission and reducing the need for secondary surgeries. Calcium phosphate ceramics, in particular, have become a key research focus due to their composition similar to human bone and excellent biocompatibility. However, calcium phosphate ceramics still suffer from insufficient mechanical properties and a mismatch between degradation and bone regeneration rates. Therefore, improving the strength and toughness of the material while maintaining biocompatibility and mitigating its degradation rate remains a critical challenge for researchers.

[0003] Hydroxyapatite whiskers (HAw), a type of calcium phosphate ceramic, possess unique advantages in bone repair due to their chemical composition's similarity to natural bone and their ability to promote osteogenic formation. However, insufficient mechanical properties and a mismatch in degradation rates remain common problems that calcium phosphate ceramics struggle to address. Metal ion doping, as an efficient strategy for structural and performance modification, involves using metal ions with specific modifying functions (such as Mg, which participates in bone formation). 2+ 、Sr 2+ Fe with catalytic or antibacterial properties 3 + Ce 3+ (etc.) replace Ca in the HAw lattice 2+ It is possible to precisely control the lattice parameters, crystal morphology, mechanical properties, and degradation rate of hydroxyapatite whiskers without destroying the crystal lattice. Therefore, improving the performance of bone repair materials by doping hydroxyapatite whiskers with metal ions is a new research direction. However, different metal ions have significant differences in ionic radius, charge valence state, and in vivo bioactivity, and there is no uniform rule for modification effects. Ion compatibility systems and optimal processes need to be developed and pre-studied in a targeted manner.

[0004] Therefore, it is necessary to propose a method for preparing modified hydroxyapatite whiskers that enhances osteogenic activity through osteoconduction in order to solve the above-mentioned technical problems. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing modified hydroxyapatite whiskers that enhances osteogenic activity through bone conduction, in order to solve the technical problems of poor mechanical properties, mismatch between degradation and osteogenic regeneration rates, and insufficient stem cell differentiation induction capacity of existing bone repair materials.

[0006] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing modified hydroxyapatite whiskers that enhance osteogenic activity through bone conduction, comprising the following steps: (1) Dissolve acetamide in ultrapure water to prepare an acetamide solution; (2) Weigh the calcium salt, strontium salt and phosphate source according to the set molar ratio, and dissolve them in the acetamide solution described in step (1) in sequence. Stir and disperse evenly to obtain a uniformly mixed precursor solution. (3) Add acid to the precursor solution obtained in step (2) and adjust the pH value to acidic to obtain the acidified precursor solution; (4) The acidified precursor solution obtained in step (3) is subjected to a hydrothermal synthesis reaction. After the reaction is completed, the precipitate is collected, aged, washed, filtered and dried to obtain a modified hydroxyapatite whisker composite material that enhances osteogenic activity.

[0007] Preferably, in step (1), the concentration of the acetamide solution is 0.8 to 1 mol / L.

[0008] Preferably, in step (2), the ratio of the total molar amount of the calcium salt and the strontium salt to the molar amount of the phosphate source is 1.60 to 1.70:1; the ratio of the molar amount of the calcium salt to the strontium salt is 0.01 to 0.02:0.0005 to 0.0015.

[0009] Preferably, in step (2), the calcium salt is calcium nitrate tetrahydrate or calcium chloride; the strontium salt is strontium nitrate or strontium chloride; and the phosphoric acid source is diammonium hydrogen phosphate or diammonium dihydrogen phosphate.

[0010] Preferably, in step (2), the stirring time is 10 to 30 minutes; the dispersion is ultrasonic dispersion, the ultrasonic time is 4 to 6 minutes, and the ultrasonic frequency is 40 to 50 kHz.

[0011] Preferably, in step (3), the acid solution is dilute nitric acid or dilute hydrochloric acid with a concentration of 0.1 to 1 mol / L, and the pH value of the solution after adjustment is 2 to 3. Since the dilute acid solution is highly volatile, the experimental environment for stirring and sonication must be ensured to be carried out in a fume hood, and the experimental personnel must wear acid-resistant gloves, masks and goggles.

[0012] Preferably, in step (4), the conditions for the hydrothermal synthesis reaction are: reaction temperature 150-180℃, reaction pressure 2-4MPa, and reaction time 4-6h; the aging time is 20-30h; the washing is performed with ultrapure water until the product is neutral; and the drying is performed at 60℃ for 10h.

[0013] The present invention also provides a modified hydroxyapatite whisker composite material that enhances osteogenic activity through osteoconduction, prepared by the method described above.

[0014] The present invention also provides an application of the modified hydroxyapatite whisker composite material described above in the preparation of bone repair materials.

[0015] Preferably, the bone repair material is used to promote osteogenic differentiation of rat mesenchymal stem cells.

[0016] The beneficial effects of this invention are: 1. Strontium ions (Sr) prepared by this invention 2+ Doping with hydroxyapatite whiskers, while ensuring that the hydroxyapatite whiskers remain unchanged and have a hexagonal cross-section, stabilizes their crystal structure, enhances their strength and toughness, and meets the actual requirements of cortical bone mechanical properties.

[0017] 2. The strontium-doped hydroxyapatite whiskers prepared in this invention significantly improve the differentiation ability of rat mesenchymal stem cells (rBMSCs) by nano-hydroxyapatite whiskers and promote osteogenic activity while ensuring low cell toxicity and stable ion release concentration. 3. The hydrothermal synthesis method used in this invention has a simple operation process and broad application prospects. Strontium is uniformly doped into the hydroxyapatite lattice through a hydrothermal reaction, resulting in a product with high purity and uniform doping. EDS characterization confirms that strontium is uniformly distributed within the whiskers, with no independent strontium compound impurity phases formed. Furthermore, XRD and TEM tests show that strontium ions replace lattice calcium ions, inducing lattice expansion, and the modification effect is stable and controllable. Attached Figure Description

[0018] Figure 1 The 3% Sr prepared in Example 1 of this invention 2+ Electron micrograph of metal ion-doped hydroxyapatite whiskers; Figure 2 The 5% Sr prepared in Example 2 of this invention 2+ Electron micrograph of metal ion-doped hydroxyapatite whiskers; Figure 3 The 10% Sr prepared in Example 3 of this invention 2+ Electron micrograph of metal ion-doped hydroxyapatite whiskers; Figure 4This is an electron microscope image of the metal ion-free hydroxyapatite whiskers prepared in Comparative Example 1 of this invention. Figure 5 The XRD patterns of hydroxyapatite prepared in Examples 2, 3 and Comparative Example 1 of this invention are shown. Figure 6 The 10% Sr prepared in Example 3 of this invention 2+ EDS image of metal ion-doped hydroxyapatite whiskers; Figure 7 The 5% Sr prepared in Example 2 of this invention 2+ TEM image of metal ion-doped hydroxyapatite whiskers; Figure 8 Alizarin red staining images of osteogenic activity of hydroxyapatite whiskers prepared in Examples 2, 3 and Comparative Example 1 of this invention. Detailed Implementation

[0019] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this application, and not all of the embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application. Example 1

[0020] Metal ion-doped hydroxyapatite whiskers (3% Sr) 2+ The preparation of ) includes the following steps: (1) Dissolve 5.91g of acetamide in ultrapure water and let it stand for later use; (2) Take a (Ca+Sr) / P molar ratio of 1.65, weigh 3.78g of calcium nitrate tetrahydrate, 0.106g of strontium nitrate, and 1.32g of diammonium hydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt, strontium salt and phosphate, while ensuring that each reagent is stirred evenly. Stir for 20min at room temperature, and then sonicate for 5min at a frequency of 45kHz to ensure that the three reagents are completely dissolved.

[0021] (3) After the solution is completely dissolved, stir it evenly at room temperature, add a certain amount of 0.1mol / L dilute nitric acid solution to adjust the pH value to 2-3; (4) Pour the above acidic solution into a high-pressure reactor and react for 4 hours at a reaction pressure of 3 MPa and a reaction temperature of 160°C to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 hours, wash it with ultrapure water to bring the pH to 7.4, filter it, and dry it at 60°C for 10 hours to obtain a hydroxyapatite composite material with the best osteogenic activity after being doped with strontium salt. Example 2

[0022] Metal ion-doped hydroxyapatite whiskers (5% Sr) 2+ The preparation of ) includes the following steps: (1) Dissolve 5.91g of acetamide in ultrapure water and let it stand for later use; (2) Take a (Ca+Sr) / P molar ratio of 1.65, weigh 3.71g of calcium nitrate tetrahydrate, 0.17g of strontium nitrate, and 1.32g of diammonium hydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt, strontium salt and phosphate, while ensuring that each reagent is stirred evenly. Stir for 20min at room temperature, and then sonicate for 5min at a frequency of 45kHz to ensure that the three reagents are completely dissolved.

[0023] (3) After the solution is completely dissolved, stir it evenly at room temperature, add a certain amount of 0.1mol / L dilute nitric acid solution to adjust the pH value to 2-3; (4) Pour the above acidic solution into a high-pressure reactor and react for 4 hours at a reaction pressure of 3 MPa and a reaction temperature of 160°C to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 hours, wash it with ultrapure water to bring the pH to 7.4, filter it, and dry it at 60°C for 10 hours to obtain a hydroxyapatite composite material with the best osteogenic activity after being doped with strontium salt. Example 3

[0024] Metal ion-doped hydroxyapatite whiskers (10% Sr) 2+ The preparation of ) includes the following steps: (1) Dissolve 5.91g of acetamide in ultrapure water and let it stand for later use; (2) Take a (Ca+Sr) / P molar ratio of 1.65, weigh 3.54g of calcium nitrate tetrahydrate, 0.32g of strontium nitrate, and 1.32g of diammonium hydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt, strontium salt and phosphate, while ensuring that each reagent is stirred evenly. Stir for 20min at room temperature, and then sonicate for 5min at a frequency of 45kHz to ensure that the three reagents are completely dissolved.

[0025] (3) After the solution is completely dissolved, stir it evenly at room temperature, add a certain amount of 0.1mol / L dilute nitric acid solution to adjust the pH value to 2-3; (4) Pour the above acidic solution into a high-pressure reactor and react for 4 hours at a reaction pressure of 3 MPa and a reaction temperature of 160°C to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 hours, wash it with ultrapure water to bring the pH to 7.4, filter it, and dry it at 60°C for 10 hours to obtain a hydroxyapatite composite material with the best osteogenic activity after being doped with strontium salt. Example 4

[0026] Metal ion-doped hydroxyapatite whiskers (3% Sr) 2+ The preparation of ) includes the following steps: (1) Dissolve 5.91g of acetamide in ultrapure water and let it stand for later use; (2) Take a (Ca+Sr) / P molar ratio of 1.65, weigh 1.78g of anhydrous calcium chloride, 0.08g of anhydrous strontium chloride and 1.15g of ammonium dihydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt, strontium salt and phosphate, while ensuring that each reagent is stirred evenly. Stir for 30min at room temperature, and then sonicate for 6min at a frequency of 45kHz to ensure that the three reagents are completely dissolved.

[0027] (3) After the solution is completely dissolved, stir it evenly at room temperature, then add a certain amount of 0.1 mol / L dilute nitric acid solution to adjust the pH value to 2; (4) Pour the above acidic solution into a high-pressure reactor and react for 5 h at a reaction pressure of 5 MPa and a reaction temperature of 180 °C to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 h, wash it with ultrapure water to pH 7.4, filter it, and dry it at 60 °C for 10 h to obtain a hydroxyapatite composite material with the best osteogenic activity after being doped with strontium salt. Example 5

[0028] Metal ion-doped hydroxyapatite whiskers (5% Sr) 2+ The preparation of ) includes the following steps: (1) Dissolve 5.91g of acetamide in ultrapure water and let it stand for later use; (2) Take a (Ca+Sr) / P molar ratio of 1.65, weigh 1.74g of anhydrous calcium chloride, 0.13g of anhydrous strontium chloride and 0.08g of ammonium dihydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt, strontium salt and phosphate, while ensuring that each reagent is stirred evenly. Stir for 30min at room temperature, and then sonicate for 6min at a frequency of 45kHz to ensure that the three reagents are completely dissolved.

[0029] (3) After the solution is completely dissolved, stir it evenly at room temperature, then add a certain amount of 0.1 mol / L dilute nitric acid solution to adjust the pH value to 2; (4) Pour the above acidic solution into a high-pressure reactor and react for 5 h at a reaction pressure of 5 MPa and a reaction temperature of 180 °C to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 h, wash it with ultrapure water to pH 7.4, filter it, and dry it at 60 °C for 10 h to obtain a hydroxyapatite composite material with the best osteogenic activity after being doped with strontium salt. Comparative Example 1

[0030] This comparative example provides a method for preparing metal ion-free hydroxyapatite whiskers, comprising the following steps: (1) Dissolve 5.91g of acetamide in ultrapure water and let it stand for later use; (2) Take a Ca / P molar ratio of 1.65, weigh 3.90g of calcium nitrate tetrahydrate and 1.32g of diammonium hydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt and phosphate, ensuring that each reagent is stirred evenly. Stir for 20min at room temperature, then sonicate for 5min at a frequency of 45kHz to ensure that the two reagents are completely dissolved.

[0031] (3) After the solution is completely dissolved, stir it evenly at room temperature, add a certain amount of 0.1mol / L dilute nitric acid solution to adjust the pH value to 2-3; (4) Pour the above acidic solution into a high-pressure reactor and react for 4 hours under the conditions of reaction pressure 3MPa and reaction temperature 160℃ to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 hours, wash it with ultrapure water to pH 7.4, filter it, and dry it at 60℃ for 10 hours to obtain hydroxyapatite whiskers without metal ion doping. Comparative Example 2

[0032] Metal ion-doped hydroxyapatite whiskers (3% Sr) 2+ The preparation of ) includes the following steps: (1) Dissolve 0.2g of sodium citrate in ultrapure water and let stand for later use; (2) Take a (Ca+Sr) / P molar ratio of 1.65, weigh 3.78g of calcium nitrate tetrahydrate, 0.106g of strontium nitrate, and 1.32g of diammonium hydrogen phosphate in advance, and dissolve each reagent in acetamide solution in the order of calcium salt, strontium salt and phosphate, while ensuring that each reagent is stirred evenly. Stir for 20min at room temperature, and then sonicate for 5min at a frequency of 45kHz to ensure that the three reagents are completely dissolved.

[0033] (3) After the solution is completely dissolved, stir it evenly at room temperature, add a certain amount of 0.1mol / L dilute nitric acid solution to adjust the pH value to 2-3; (4) Pour the above acidic solution into a high-pressure reactor and react for 4 hours at a reaction pressure of 3 MPa and a reaction temperature of 160°C to obtain a white-gray flocculent precipitate. Let the precipitate stand for 24 hours, wash it with ultrapure water to bring the pH to 7.4, filter it, and dry it at 60°C for 10 hours to obtain a hydroxyapatite composite material with the best osteogenic activity after being doped with strontium salt. Test Example 1:

[0034] Figure 1 , 23 and 4 are the 3% Sr prepared in Example 1 of this invention. 2+ The 5% Sr prepared in Example 2 2+ The 10% Sr prepared in Example 3 2+ Electron microscopy images of metal ion-free hydroxyapatite whiskers prepared in Comparative Example 1. As shown in the figures, Sr... 2+ The doped sample still consisted mainly of whiskers, but with increasing doping concentration, whisker breakage, dendrite fracture, and fragmentation gradually increased, indicating that higher Sr content... 2+ Doping reduces the integrity of whisker morphology. Notably, a more regular hexagonal cross-sectional structure can be observed in the 10Sr-HAw sample, consistent with the hexagonal crystal system of hydroxyapatite, and exhibiting growth characteristics along the c-axis.

[0035] Figure 5 The figures show the XRD patterns of hydroxyapatite prepared in Examples 2, 3, and Comparative Example 1 of this invention; as can be seen from the figures, Sr is doped into HAw. 2+ Later, due to Sr 2+ and Ca 2+ Since they are isovalent cations with similar radii, isomorphic substitution can be achieved, therefore HAw retains the hydroxyapatite crystal form; and because Sr... 2+ The ionic radius is greater than that of Ca. 2+ After substitution, lattice expansion and interplanar spacing increase; according to Bragg's equation 2dsinθ=nλ, the increase in interplanar spacing d will decrease the diffraction angle 2θ, which is manifested as the positions of the diffraction peaks of the principal crystal planes such as (210), (211), and (300) shifting to the left, and with the increase of Sr 2+ The more the doping concentration increases, the more pronounced the leftward shift becomes. This argument aligns with the shift direction shown in the figure, proving that Sr... 2+ Successfully entered the hydroxyapatite lattice; doping successful.

[0036] Figure 6 The 10% Sr prepared in Example 3 of this invention 2+ EDS spectra of metal ion-doped hydroxyapatite whiskers; as can be seen from the figure, Sr 2+ Hydroxyapatite can be successfully incorporated and evenly distributed. Furthermore, it exhibits excellent distribution across its hexagonal cross-section, further demonstrating the superior properties of Sr. 2+ The successful doping of Sr further confirms... 2+ It enters the interior of the crystal lattice to form a uniform solid solution, rather than forming an independent strontium compound phase that coats the surface.

[0037] Figure 7 The 5% Sr prepared in Example 2 of this invention 2+TEM image of metal ion-doped hydroxyapatite whiskers; the interplanar spacing d = 0.376 nm corresponding to the stripe structure of the (022) crystal plane in the image is significantly increased compared to the interplanar spacing of the (002) crystal plane of pure HAw (approximately 0.344 nm). This is due to the Sr 2+ The ionic radius is greater than that of Ca. 2+ After substitution, lattice expansion and interplanar spacing occur. Test Example 2:

[0038] The osteogenic differentiation capacity of the obtained samples was tested using the following steps: Osteogenic differentiation capacity was quantitatively evaluated by Alizarin Red (ARS) staining. rBMSCs were seeded at 1×10⁻⁶ cells / well in 24-well plates. After adhesion, the medium was replaced with osteogenic induction medium (containing 10⁻⁸ M dexamethasone, 10 mM β-glycerophosphate sodium, and 50 μg / mL ascorbic acid). Simultaneously, pure hydroxyapatite whiskers without metal ion doping (Comparative Example 1) and metal ion doped hydroxyapatite whiskers (5% Sr) (Example 2) were added. 2+ ), and Example 3 Metal ion doped hydroxyapatite whiskers (10% Sr ), and 2+ Material suspension or extract. After 3 and 7 days of induction culture, the reaction was terminated: wash twice with PBS, fix with 4% paraformaldehyde at room temperature for 30 min, rinse three times with distilled water; add 0.5% ARS solution (pH 4.2) and stain at room temperature for 30 min, gently rinse with running water to remove unbound dye, and terminate the reaction by immersion in PBS. Observe the density and distribution of mineralized nodules under a stereomicroscope, or elute with 10% hexadecylpyridine chloride solution and measure the absorbance at 570 nm to quantitatively analyze the amount of calcium deposition.

[0039] Figure 8 Alizarin Red staining assays were performed on the osteogenic activity of hydroxyapatite whiskers prepared in Examples 2, 3, and Comparative Example 1 of this invention. The results showed that all material groups exhibited a clear time-dependent and mineralization-enhancing trend: at 3 days, the experimental group showed a lighter red staining, with no significant difference from the control group; however, at 7 days, the staining intensity and the number of mineralized nodules in the experimental group were significantly enhanced, indicating that the mineralization deposition level increased significantly over time. This means that the prepared metal ion-doped hydroxyapatite whisker material significantly promoted the osteogenic activity of rat mesenchymal stem cells (rBMSCs).

[0040] The embodiments of the present invention use the following parameters for preparation: acetamide concentration of 0.8 mol / L or 1 mol / L, total calcium and strontium cation to phosphorus molar ratio of 1.60 or 1.70, calcium salt: strontium salt ratio of 0.01:0.0005 or 0.02:0.0015, stirring time of 10 min, ultrasonic time of 4 min, ultrasonic frequency of 40 kHz or 50 kHz, concentration of 1 mol / L dilute acid, hydrothermal temperature of 150℃, hydrothermal pressure of 2 MPa or 4 MPa, hydrothermal reaction time of 6 h, and precipitate aging of 20 h or 30 h. All of these combinations can yield modified hydroxyapatite whiskers with comparable performance and the same osteopromoting effect.

[0041] The specific embodiments of the invention have been described in detail above, but these are merely examples, and the invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications or substitutions to the invention are also within the scope of this invention. Therefore, all equivalent transformations, modifications, and improvements made without departing from the spirit and principles of this invention should be included within the scope of this invention.

Claims

1. A method for preparing modified hydroxyapatite whiskers that enhance osteogenic activity through bone conduction, characterized in that, Includes the following steps: (1) Dissolve acetamide in ultrapure water to prepare an acetamide solution; (2) Weigh the calcium salt, strontium salt and phosphate source according to the set molar ratio, and dissolve them in the acetamide solution described in step (1) in sequence. Stir and disperse evenly to obtain a uniformly mixed precursor solution. (3) Add acid to the precursor solution obtained in step (2) and adjust the pH value to acidic to obtain the acidified precursor solution; (4) The acidified precursor solution obtained in step (3) is subjected to a hydrothermal synthesis reaction. After the reaction is completed, the precipitate is collected, aged, washed, filtered and dried to obtain a modified hydroxyapatite whisker composite material that enhances osteogenic activity.

2. The preparation method according to claim 1, characterized in that, In step (1), the concentration of the acetamide solution is 0.8 to 1 mol / L.

3. The preparation method according to claim 1, characterized in that, In step (2), the ratio of the total molar amount of the calcium salt and the strontium salt to the molar amount of the phosphate source is 1.60 to 1.70:1; the ratio of the molar amount of the calcium salt to the strontium salt is 0.01 to 0.02:0.0005 to 0.0015.

4. The preparation method according to claim 1, characterized in that, In step (2), the calcium salt is calcium nitrate tetrahydrate or calcium chloride; the strontium salt is strontium nitrate or strontium chloride; and the phosphoric acid source is diammonium hydrogen phosphate or diammonium dihydrogen phosphate.

5. The preparation method according to claim 1, characterized in that, In step (2), the stirring time is 10 to 30 minutes; the dispersion is ultrasonic dispersion, the ultrasonic time is 4 to 6 minutes, and the ultrasonic frequency is 40 to 50 kHz.

6. The preparation method according to claim 1, characterized in that, In step (3), the acid solution is dilute nitric acid or dilute hydrochloric acid with a concentration of 0.1 to 1 mol / L, and the pH value of the solution after adjustment is 2 to 3.

7. The preparation method according to claim 1, characterized in that, In step (4), the conditions for the hydrothermal synthesis reaction are: reaction temperature 150-180℃, reaction pressure 2-4MPa, and reaction time 4-6h; the aging time is 20-30h; the washing is done with ultrapure water until the product is neutral; and the drying is done at 60℃ for 10h.

8. A modified hydroxyapatite whisker composite material for enhancing osteogenic activity by means of the method described in any one of claims 1-7.

9. The application of the modified hydroxyapatite whisker composite material as described in claim 8 in the preparation of bone repair materials.

10. The application according to claim 9, characterized in that, The bone repair material is used to promote osteogenic differentiation of rat mesenchymal stem cells.